Roaring lions and chirruping lemurs: How the brain encodes sound objects in space. (August 2015) - Clarke, Stephanie; Geiser, Eveline
Abstract: The dual-stream model of auditory processing postulates separate processing streams for sound meaning and for sound location. The present review draws on evidence from human behavioral and activation studies as well as from lesion studies to argue for a position-linked representation of sound objects that is distinct both from the position-independent representation within the ventral/What stream and from the explicit sound localization processing within the dorsal/Where stream. Highlights: Sound objects are encoded in a location-independent and in a location-linked fashion. Repetition priming, streaming and lesion studies provide concurring evidence. Left superior temporal and inferior prefrontal areas carry location-linked encoding. Parietal lesions impair the ability to localize sounds but not to segregate them by spatial cues.